A Website Created to Support English-speaking Patients from Eastern Regions in Quebec Traveling Away from Home for Medical Services - Community Health and Social Services Network (CHSSN) (2017)

A Needs Assessment : Better Understanding the Current Situation of the Senior Population - Burke, Helena; Craig, Lisa; Richardson, Mary (Council for Magdalen Islanders (CAMI), 2017)
This needs assessment was conducted as part of a community development process in the English-speaking community of Grosse-Ile, on the Magdalen Islands, Quebec. It is part of the follow- up to a community portrait that was developed through a participatory process in early 2015. The process involved the mobilization and engagement of a number of local stakeholders as well as community residents who expressed their views on a number of different themes. One of the issues that was highlighted by community members as a concern, even a priority, was that of the aging population within the ESC, having access to few services and limited support for caregivers.
Keywords: Official Language Minority Community (OLMC)

Une évaluation des besoins : mieux comprendre la situation actuelle des aînés - Burke, Helena; Craig, Lisa; Richardson, Mary (Council for Magdalen Islanders (CAMI), 2017)
Cette évaluation des besoins a été menée dans le cadre d’un processus de développement communautaire dans la communauté anglophone de Grosse-Île, aux Îles-de-la-Madeleine, Québec. Elle fait partie du suivi d’un portrait communautaire qui a été élaboré par le biais d’un processus participatif au début de 2015. Le processus a impliqué la mobilisation et l’engagement de plusieurs intervenants locaux ainsi que de résidents de la communauté qui ont exprimé leurs opinions sur un bon nombre de thèmes. L’un des enjeux qui a été souligné par les membres de la communauté comme une préoccupation, voire une priorité, était celui du vieillissement de la population au sein de la CAI, ayant peu de services et un soutien limité aux proches aidants.
Keywords: Official Language Minority Community (OLMC)